An AMP-activated protein kinase complex with two distinctive alpha subunits is involved in nutritional stress responses in Trypanosoma cruzi. - Tamara Sternlieb; Alejandra C Schoijet; Patricio D Genta; Salomé C Vilchez Larrea; Guillermo D Alonso (Public Library of Science (PLoS), 2021)
Trypanosoma cruzi, the etiological agent of Chagas disease, has a digenetic life cycle. In its passage from the insect vector to the mammalian host, and vice versa, it must be prepared to cope with abrupt changes in environmental conditions, such as carbon source, pH, temperature and osmolarity, in order to survive. Sensing and signaling pathways that allow the parasite to adapt, have unique characteristics with respect to their hosts and other free-living organisms. Many of the canonical proteins involved in these transduction pathways have not yet been found in the genomes of these parasites because they present divergences either at the functional, structural and/or protein sequence level. All of this makes these pathways promising targets for therapeutic drugs. The AMP-activated protein kinase (AMPK) is a serine/threonine kinase activated by environmental stresses such as osmotic stress, hypoxia, ischaemia and exercise that results in reduction of ATP and increase of AMP levels. Thus, AMPK is regarded as a fuel gauge, functioning both as a nutrient and an energy sensor, to maintain energy homeostasis and, eventually, to protect cells from death by nutrient starvation. In the present study we report the characterization of AMPK complexes for the first time in T. cruzi and propose the function of TcAMPK as a novel regulator of nutritional stress in epimastigote forms. We show that there is phosphotransferase activity specific for SAMS peptide in epimastigotes extracts, which is inhibited by Compound C and is modulated by carbon source availability. In addition, TcAMPKα2 subunit has an unprecedented functional substitution (Ser x Thr) at the activation loop and its overexpression in epimastigotes led to higher autophagic activity during prolonged nutritional stress. Moreover, the over-expression of the catalytic subunits resulted in antagonistic phenotypes associated with proliferation. Together, these results point to a role of TcAMPK in autophagy and nutrient sensing, key processes for the survival of trypanosomatids and for its life cycle progression.